Sociodemographic variations in the contribution of secondary drug prevention to stroke survival at middle and older ages: cohort study. (16th April 2009) - Raine, Rosalind; Wong, Wun; Ambler, Gareth; Hardoon, Sarah; Petersen, Irene; Morris, Richard; Bartley, Mel; Blane, David
Abstract : Objectives To determine the extent to which secondary drug prevention for patients with stroke in routine primary care varies by sex, age, and socioeconomic circumstances, and to quantify the effect of secondary drug prevention on one year mortality by sociodemographic group. Design Cohort study using individual patient data from the health improvement network primary care database. Setting England. Participants 12 830 patients aged 50 or more years from 113 general practices who had a stroke between 1995 and 2005 and who survived the first 30 days after the stroke. Main outcome measures Multivariable associations between odds of receiving secondary prevention after a stroke, and sex, age group, and socioeconomic circumstances; hazard ratios for all cause mortality from 31 days after the stroke and within the first year among patients receiving treatment and by social group; and probabilities of one year mortality for social factors of interest and treatment. Results Only 25.6% of men and 20.8% of women received secondary prevention. Receipt of secondary prevention did not vary by socioeconomic circumstances or by sex. Older patients were, however, substantially less likely to receive treatment. The adjusted odds ratio for 80-89 year olds compared with 50-59 year olds was 0.53 (95% confidence interval 0.41 to 0.69). This was because older people were less likely to receive lipid lowering drugs—for example, the adjusted odds ratio for 80-89 year olds compared with 50-59 year olds was 0.44 (95% confidence interval 0.33 to 0.59). Secondary prevention was associated with a 50% reduction in mortality risk (adjusted hazard ratio 0.50, 95% confidence interval 0.42 to 59). On average, mortality within the first year was 5.7% for patients receiving treatment compared with 11.1% for patients not receiving treatment. There was little evidence that the effect of treatment differed between the social groups examined. Conclusion Under-treatment among older people with stroke in routine primary care cannot be justified given the lack of evidence on variations in effectiveness of treatment by age.